Modern building materials and their investigation methods - Gailius, Albinas; Kinuthia, John (Journal of Civil Engineering and Management, 2009)
„Modern building materials and their investigation methods" Journal of Civil Engineering and Management, 15(2), p. 129-130First Published Online: 14 Oct 2010